PENGARUH PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Pada PT. PLN (Persero) Unit Empang) - Ika Fitriyani; Vivin Fitryani; Muhammad Kevin (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
The purpose of this study was to analyze the effect of occupational health and safety (K3) on the work productivity of employees at PT. PLN (Persero) Empang Unit. This type of research is a quantitative descriptive research. The population in this study were employees of PT. PLN (Persero) Empang Unit. The number of samples is 84 samples. The data analysis method used in this research is multiple linear regression analysis, t test, F test and determinant coefficient test (R2). Based on the results of the analysis that has been carried out, it is known that occupational health (X1) and work safety (X2) have a positive and significant effect on the work productivity of PT. PLN Unit Empang (Y), either partially or simultaneously. The results of the R2 test show that the effect of occupational health (X1) and work safety (X2) variables on the work productivity of PT. PLN Unit Empang (Y) is 94.2%, while the remaining 5.8% is influenced by other factors not examined in this study.